Efficacy and safety of semaglutide compared with liraglutide and placebo for weight loss in patients with obesity: a randomised, double-blind, placebo and active controlled, dose-ranging, phase 2 trial. Issue 10148 (25th August 2018) - O'Neil, Patrick M; Birkenfeld, Andreas L; McGowan, Barbara; Mosenzon, Ofri; Pedersen, Sue D; Wharton, Sean; Carson, Charlotte Giwercman; Jepsen, Cecilie Heerdegen; Kabisch, Maria; Wilding, John P H
Summary: Background: Obesity is a major public health issue, and new pharmaceuticals for weight management are needed. Therefore, we evaluated the efficacy and safety of the glucagon-like peptide-1 (GLP-1) analogue semaglutide in comparison with liraglutide and a placebo in promoting weight loss. Methods: We did a randomised, double-blind, placebo and active controlled, multicentre, dose-ranging, phase 2 trial. The study was done in eight countries involving 71 clinical sites. Eligible participants were adults (≥18 years) without diabetes and with a body-mass index (BMI) of 30 kg/m 2 or more. We randomly assigned participants (6:1) to each active treatment group (ie, semaglutide [0·05 mg, 0·1 mg, 0·2 mg, 0·3 mg, or 0·4 mg; initiated at 0·05 mg per day and incrementally escalated every 4 weeks] or liraglutide [3·0 mg; initiated at 0·6 mg per day and escalated by 0·6 mg per week]) or matching placebo group (equal injection volume and escalation schedule to active treatment group) using a block size of 56. All treatment doses were delivered once-daily via subcutaneous injections. Participants and investigators were masked to the assigned study treatment but not the target dose. The primary endpoint was percentage weight loss at week 52. The primary analysis was done using intention-to-treat ANCOVA estimation with missing data derived from the placebo pool. This study is registered with ClinicalTrials.gov, number NCT02453711 . Findings: Between Oct 1, 2015, and Feb 11, 2016, 957 individuals were randomly assigned (102–103 participants per active treatment group and 136 in the pooled placebo group). Mean baseline characteristics included age 47 years, bodyweight 111·5 kg, and BMI 39·3 kg/m 2 . Bodyweight data were available for 891 (93%) of 957 participants at week 52. Estimated mean weight loss was −2·3% for the placebo group versus −6·0% (0·05 mg), −8·6% (0·1 mg), −11·6% (0·2 mg), −11·2% (0·3 mg), and −13·8% (0·4 mg) for the semaglutide groups. All semaglutide groups versus placebo were significant (unadjusted p≤0·0010), and remained significant after adjustment for multiple testing (p≤0·0055). Mean bodyweight reductions for 0·2 mg or more of semaglutide versus liraglutide were all significant (−13·8% to −11·2% vs −7·8%). Estimated weight loss of 10% or more occurred in 10% of participants receiving placebo compared with 37–65% receiving 0·1 mg or more of semaglutide (p<0·0001 vs placebo). All semaglutide doses were generally well tolerated, with no new safety concerns. The most common adverse events were dose-related gastrointestinal symptoms, primarily nausea, as seen previously with GLP-1 receptor agonists. Interpretation: In combination with dietary and physical activity counselling, semaglutide was well tolerated over 52 weeks and showed clinically relevant weight loss compared with placebo at all doses. Funding: Novo Nordisk A/S.